2014
DOI: 10.1038/ncomms4956
|View full text |Cite
|
Sign up to set email alerts
|

Mobile elements drive recombination hotspots in the core genome of Staphylococcus aureus

Abstract: Horizontal gene transfer is an important driver of bacterial evolution, but genetic exchange in the core genome of clonal species, including the major pathogen Staphylococcus aureus, is incompletely understood. Here we reveal widespread homologous recombination in S. aureus at the species level, in contrast to its near-complete absence between closely related strains. We discover a patchwork of hotspots and coldspots at fine scales falling against a backdrop of broad-scale trends in rate variation. Over megaba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
126
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(147 citation statements)
references
References 70 publications
(113 reference statements)
17
126
1
Order By: Relevance
“…As might be expected, the power and accuracy of these algorithms are maximized when a donor sequence is included (imparting the source of homology between unrelated lineages) and when the recombinant sequence introduces many polymorphic nucleotides (43,46). Therefore, homoplasiescharacters that are inferred to be shared by, but not present in, the common ancestor of lineages-represent robust signals of recombination and provide a very fine (i.e., per nucleotide site) resolution of recombination maps, as have been performed recently for sequenced strains of Staphylococcus aureus (47). Homoplasic sites allow detection of internal recombination events (i.e., recombinant polymorphic sites that are included in the dataset) but ignore polymorphic sites that were introduced by external, unsampled sources.…”
Section: How To Best Assess the Impact Of Recombination On E Coli Evmentioning
confidence: 99%
See 1 more Smart Citation
“…As might be expected, the power and accuracy of these algorithms are maximized when a donor sequence is included (imparting the source of homology between unrelated lineages) and when the recombinant sequence introduces many polymorphic nucleotides (43,46). Therefore, homoplasiescharacters that are inferred to be shared by, but not present in, the common ancestor of lineages-represent robust signals of recombination and provide a very fine (i.e., per nucleotide site) resolution of recombination maps, as have been performed recently for sequenced strains of Staphylococcus aureus (47). Homoplasic sites allow detection of internal recombination events (i.e., recombinant polymorphic sites that are included in the dataset) but ignore polymorphic sites that were introduced by external, unsampled sources.…”
Section: How To Best Assess the Impact Of Recombination On E Coli Evmentioning
confidence: 99%
“…There are many classes of accessory genes, such as mobile elements (e.g., prophages, transposons), which are known to be associated with elevated rates of recombination. In both E. coli and S. aureus, it was recently shown that core genes in the vicinity of accessory genes or mobile elements experience higher recombination rates (44,47). Chromosome loci with the highest homologous recombination rates (recombination hotspots) have also been associated with nonmobilizable genomic islands in E. coli (e.g., the fim locus).…”
Section: Beyond the Core Genomementioning
confidence: 99%
“…To explore whether recombination was due to donors from the same lineage, we classed homoplasic SNPs as those confined to a certain lineage as opposed to those found in multiple lineages. The number of such positions were scaled by the synapomorphic SNPs in a 10-kb sliding window at 1-kb intervals across the genome, similar to the method previously described (Everitt et al 2014) …”
Section: Recombination Analysismentioning
confidence: 99%
“…Our results provided no evidence for the mobilization of sequences flanking the element's integration site. Thus, the mechanism responsible for the strong signal of chromosomal recombination adjacent to the integration site of ICE6013 in S. aureus strain MRSA252 (20) requires further study. The frequencies of ICE6013 conjugation between some strains approached that of the well-studied conjugative plasmid pGO1 (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…ICE6013 was noted to have relatively low integration site specificity, since the 3-bp target site that forms a direct repeat upon integration was variable in sequence and integration occurred at 11 different loci among 12 different strains of S. aureus (13). According to one analysis, the ICE6013 integration site in strain MRSA252 is adjacent to the strongest hot spot for recombination in the S. aureus chromosome (20). However, neither the integration site preference nor the conjugative transfer of ICE6013 or its flanking chromosomal sequences has been experimentally demonstrated.…”
mentioning
confidence: 99%